Sesamum albidiflorum (Pedaliaceae), a new species from the savanna, Nigeria - Zhigila, Daniel A.; Abdul, Suleiman D.; Sawa, Fatima B.j. (Phytotaxa, 2026)
A new species of Sesamum (Pedaliaceae), Sesamum albidiflorum sp. nov., is described and illustrated from the savanna, Nigeria. The species is morphologically similar to the widespread African taxa S. indicum, S. radiatum, and S. sesamoides, but is readily distinguished by its entirely white flowers, glabrous calyx lobes, shorter pedicels, and fewer seeds per capsule. Phylogenetic analyses based on nuclear and plastid DNA markers indicate S. albidiflorum as sister to S. sesamoides, supporting its recognition as a distinct species. Comparative analysis of seed coat micromorphology further corroborates its taxonomic distinctiveness. Detailed morphological comparisons with regional floras, herbarium specimens (including type material), confirm the uniqueness of S. albidiflorum within the genus. Information on its distribution, habitat, phenology, and diagnostic characteristics is provided, along with a preliminary conservation assessment based on IUCN Red List criteria. The description of S. albidiflorum highlights the existing underestimation of plant diversity in West Africa and underscores the value of integrative taxonomic approaches that combine morphology, micromorphology, and molecular phylogenetics.